Religieus geloof en religieuze verbondenheid in Europa - Jan Reitsma; Ben Pelzer; Peer Scheepers; Hans Schilderman (Religie & Samenleving, 2013)
This paper investigates (trends and determinants of) individual combinations of religious believing and belonging in Europe from a cross-national and longitudinal perspective. Individual level data for the period 1981-2007 in 42 countries derived from the European Values Survey and the European Social Survey are harmonised and enriched with contextual characteristics, constituting a more comprehensive data base for Europe than any previous research. Complementary hypotheses from modernization and market theories are derived systematically and tested rigorously. We find differential trends. In western societies, the popularity of secularity and consistent religiosity has persisted. In former communist societies, the popularity of consistent religiosity has increased whereas secularity has decreased. In both western and former communist societies, solitary religiosity has been a clear yet small phenomenon, somewhat increasing in western societies and somewhat decreasing in former communist societies. A crucial hypothesis derived from modernization theories, stating that financial and social security would decrease consistent religiosity is empirically supported.